Perawatan Metode Kanguru pada Bayi Baru Lahir dengan Berat Badan Lahir Rendah - Fajrin, Dessy Hidayati; Puspita Satrya Putri, Ayu (Jurnal Sains dan Teknologi Kesehatan, 2023)
Abstract. Low birth weight infants are at risk for hypothermia. Kangaroo Method treatment can increase the baby's body temperature, and reduce the occurrence of hypothermia in low birth weight babies. The Kangaroo Mother Care (KMC) is an early care method with skin touch between mother and newborn in the kangaroo position. The purpose of this study was to provide collaborative midwifery care in cases of pathology and complications in By. Mrs. T low birth weight with hypothermia using the kangaroo method. This research was conducted using descriptive qualitative with a case study approach and field observation at RSUD Kabupaten Kubu Raya. The results obtained from this study are there is an increase in temperature in infants who experience hypothermia after performing midwifery care with the kangaroo method. The conclusion obtained is that the Kangaroo Mother Care can be used to overcome hypothermia in low birth weight babies.